PERAN TATA KELOLA PERUSAHAAN PADA PENGUNGKAPAN MODAL INTELEKTUAL - Fadhil Rahandika; Totok Dewayanto (Diponegoro Journal of Accounting, 2019)
The aim of this study is to examine the role of corporate governance in intellectual capital disclosure. This study used firm performance, capital structure and fim size as control variable. The population in this study consists of manufacturing companies in Indonesia Stock Exchange for the period 2015 - 2017. Sample determined with purposive sampling method. Total sample of this research is 381 companies.This study used multiple regression analysis for hypotheses testing. The results of this study show that board size, the propotion of independent commissioner, blockholder ownership and government ownership has positive effect and significant on intellectual capital disclosure. Meanwhile, board tenure has no effect on on intellectual capital disclosure